A project on developing monoecious pistachio (Pistacia vera L.) populations and determination of sex mechanism in Pistacia - Kafkas S.; Açar I.; Gozel H. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
This project aims to develop monoecious P. vera cultivars, and to determine sex mechanism and inheritance in Pistacia by inter- and intra-specific hybridization using these trees. Two monoecious P. atlantica genotypes were used both as male and female parents: One P. atlantica genotype and two P. vera cultivars ('Ohadi' and 'Siirt') were used as other female parents. One P. atlantica and one P. vera genotypes were used as male parents as well. The plants of 2001 crosses are now one year old and they were morphologically characterized. The seeds from 2002 crosses were germinated and transplanted into plastic bags. The orchard will be established with approximately 3000 plants. About 1500-1600 plants are hybrids between P. vera cultivars and monoecious P. atlantica genotypes and the rest of them are from the other combinations. The breeding orchard will be set up in the Pistachio Research Institute in Gaziantep province with drip irrigation in the autumn of 2003.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)